Games for health in the home: gaming and older adults in the digital age of healthcare - Hall, Amanda K.; Marston, H. (Handbook of Smart Homes, Health Care, and Well-being, 2014)
This chapter provides an overview of current research on digital health games and health benefits derived from game play in the home setting by an older adult population. Initially, this chapter presents the current problems of an aging population and a series of gaming trends, game genres, and technology used by older adults are described. This chapter further ascertains previous works, primarily reviews (narrative and systematic), to establish the current stance of utilizing digital games for health among older adults and assesses quality-of-life benefits. Aggregated recommendations across all the reviewed studies are listed and a comprehensive standard digital health game classification system is proposed. Games for health taxonomy and respective technologies are described, in particular the nature of engagement by users. Finally, recommendations for future research on games for health in the home are provided.